2003
DOI: 10.1074/jbc.m303273200
|View full text |Cite
|
Sign up to set email alerts
|

Ku Stimulation of DNA Ligase IV-dependent Ligation Requires Inward Movement along the DNA Molecule

Abstract: The DNA ligase IV⅐XRCC4 complex (LX) functions in DNA non-homologous-end joining, the main pathway for double-strand break repair in mammalian cells. We show that, in contrast to ligation by T4 ligase, the efficiency of LX ligation of double-stranded (ds) ends is critically dependent upon the length of the DNA substrate. The effect is specific for ds ligation, and LX/DNA binding is not influenced by the substrate length. Ku stimulates LX ligation at concentrations resulting in 1-2 Ku molecules bound per substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 28 publications
(39 reference statements)
5
60
0
Order By: Relevance
“…In support of this we have observed that adenylation activity is only detectable after treatment with PPi suggesting that the majority of the DNA ligase IV/Xrcc4 complexes expressed in insect cells are pre-adenylated [22] (data not shown). Additionally, we have found that non-adenylatable DNA ligase IV complexes are expressed at low levels in insect cells.…”
Section: Mutational Changes Within Motif Va Impact Upon Dna Ligase IVsupporting
confidence: 60%
See 2 more Smart Citations
“…In support of this we have observed that adenylation activity is only detectable after treatment with PPi suggesting that the majority of the DNA ligase IV/Xrcc4 complexes expressed in insect cells are pre-adenylated [22] (data not shown). Additionally, we have found that non-adenylatable DNA ligase IV complexes are expressed at low levels in insect cells.…”
Section: Mutational Changes Within Motif Va Impact Upon Dna Ligase IVsupporting
confidence: 60%
“…[20,22] Human Xrcc4 was obtained from pCIneo-Xrcc4 by digestion with EcoRI and NotI, and inserted into the multiple cloning site of pFasBac Dual vector (Invitrogen) generating pFastBacDual-Xrcc4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ku heterodimer (orange and red) binds DNA ends exposed by a double-strand break, recruits DNA-PKcs and forms the catalytically active protein kinase DNA-PK. DNA Ligase IV is recruited as part of a complex with XRCC4 and XLF and requires inward translocation of Ku to permit binding of DNA Ligase IV complex [17]. End-ligation is catalyzed by DNA Ligase IV.…”
Section: Resultsmentioning
confidence: 99%
“…When bound to DNA, Ku recruits DNA-PKcs and activates its kinase activity (10,11). The XRCC4⅐Lig4 protein complex is recruited to the DNA ends to complete ligation (4,5,12). An additional protein, Artemis, which has nuclease activity and can open DNA hairpin intermediates with DNA-PKcs during V(D)J recombination (13), has also been shown to be involved in both NHEJ and V(D)J recombination (14,15).…”
mentioning
confidence: 99%